Forming and implementing community advisory boards in low- and middle-income countries: a scoping review - Yang Zhao; Thomas Fitzpatrick; Bin Wan; Suzanne Day; Allison Mathews; Joseph D. Tucker (2019)
Abstract Background Community advisory boards (CABs) have expanded beyond high-income countries (HICs) and play an increasing role in low- and middle-income country (LMIC) research. Much research has examined CABs in HICs, but less is known about CABs in LMICs. The purposes of this scoping review are to examine the creation and implementation of CABs in LMICs, including identifying frequently reported challenges, and to discuss implications for research ethics. Methods We searched five databases (PubMed, Embase, Global Health, Scopus, and Google Scholar) for publications describing or evaluating CABs in LMICs. Two researchers independently reviewed articles for inclusion. Data related to the following aspects of CABs were extracted from included publications: time, country, financial support, research focus, responsibilities, and challenges. Thematic analyses were used to summarize textual data describing challenges. Results Our search yielded 2005 citations, 83 of which were deemed eligible for inclusion. Most studies (65) were published between 2010 and 2017. Upper-middle-income countries were more likely to have studies describing CABs, with South Africa (17), China (8), and Thailand (7) having the greatest numbers. The United States National Institutes of Health was the main source of financial support for CABs. Many CABs (53/88, 60%) focused on HIV research. Thirty-four studies reported how CABs influenced the informed consent process for clinical trials or other aspects of research ethics. CAB responsibilities were related to clinical trials, including reviewing study protocols, educating local communities about research activities, and promoting the ethical conduct of research. Challenges faced by CABs included the following: incomplete ethical regulations and guidance; limited knowledge of science among members of communities and CABs; unstable and unbalanced power relationships between researchers and local communities; poor CAB management, including lack of formal participation structures and absence of CAB leadership; competing demands for time that limited participation in CAB activities; and language barriers between research staff and community members. Several challenges reflected shortcomings within the research team. Conclusions Our findings examine the formation and implementation of CABs in LMICs and identify several ethical challenges. These findings suggest the need for further ethics training among CAB members and researchers in LMICs.